Hide text in an image using Blowfish algorithm and development of least significant bit technique - Kareem Salim, Sarah; Majid Msallam, Mohammed; Ismail Olewi, Huda (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Recently, there is increasing interest in data transfer between many different devices. Data must be encrypted before being sent so that the intended receiver can only read it to prevent unauthorized access and processing of a secret message. This paper suggests two levels of security to secure import messages that are sent via the internet. A secret text is encrypted by a Blowfish algorithm, then the secret text is hidden in an image by the least significant bit (LSB) technique. The LSB method of concealing important information was developed to conceal at least the first of at least two bits, depending on the cover data. The resolution of an image is raised in our work where the sender selects a stego image with a high peak signal to noise ratio (PSNR). The receiver knows all the necessary information for decoding by the first nine pixels. The PSNR is used for evaluating the resolution of the image to check robustness at sending. The number of PSNR illustrates in our proposal that the resolution of the image is near the original LSB technique, but the embedding is more randomly robust in steganography.